2010
DOI: 10.1007/s00449-010-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

β-Galactosidase production by the psychrotolerant yeast Guehomyces pullulans 17-1 isolated from sea sediment in Antarctica and lactose hydrolysis

Abstract: A psychrotolerant yeast Guehomyces pullulans 17-1 was isolated from sea sediment in Antarctica. It was found that it could yield both extracellular and cell-bound β-galactosidase. After optimization of the medium and cultivation conditions, it was found that the yeast strain produced over 17.2 U mL⁻¹ of β-galactosidase activity within 120 h at the flask level while the yeast strain produced over 25.3 U mL⁻¹ of β-galactosidase activity within 144 h during the 2-L fermentation. This is the highest β-galactosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…In our previous studies [7], it was found that the psychrotolerant yeast G. pullulans 17-1 isolated from sea sediment in Antarctica could produce over 17.2 U/ml of β-galactosidase activity within 120 h at the flask level. In order to further enhance β-galactosidase activity produced by the yeast strain, its cells were treated using NTG as described in "Materials and Methods".…”
Section: Mutagenesis and Screening For β-Galactosidase Overproducermentioning
confidence: 99%
“…In our previous studies [7], it was found that the psychrotolerant yeast G. pullulans 17-1 isolated from sea sediment in Antarctica could produce over 17.2 U/ml of β-galactosidase activity within 120 h at the flask level. In order to further enhance β-galactosidase activity produced by the yeast strain, its cells were treated using NTG as described in "Materials and Methods".…”
Section: Mutagenesis and Screening For β-Galactosidase Overproducermentioning
confidence: 99%
“…With optimizing the medium and cultivation conditions, the yeast strain G. pullulans 17-1 could produce over 17.2 U mL -1 of β-galactosidase activity, which was the highest in the wild type yeasts reported so far (Song et al, 2010).…”
Section: Potential Applications Of the Yeasts Isolated From The Antarmentioning
confidence: 94%
“…To isolate yeasts, 2.0 g of the sediments was suspended in 20.0 mL of YPD medium (20.0 g L -1 polypeptone, 20.0 g L -1 glucose and 10.0 g L -1 yeast extract) prepared with seawater and supplemented with 0.5 g L -1 chloramphenicol and cultivated at 15℃ for 5 d. Then the sample was diluted and plated on the YPD plates with 0.5 g L -1 chloramphenicol and the plates were incubated at 15℃ for 5 d. Different yeast colonies from the plates were transferred to the YPD slants (Song et al, 2010).…”
Section: Isolation Of Yeastsmentioning
confidence: 99%
“…Several other cold-active ␤-galactosidases have been identified and characterized; these include those from Arthrobacter psychrolactophilus strain F2 (Nakagawa et al, 2007); Arthrobacter sp. 20B (Białkowska et al, 2009); and the psychrotolerant yeast Guehomyces pullulans 17-1 (Song et al, 2010). Some of these enzymes may be used in lactose hydrolysis in the future.…”
Section: Enzymes From Cold-adapted Organismsmentioning
confidence: 99%